Proceedings of the 3rd International Conference on Early Childhood Education (ICECE 2016) 2017
DOI: 10.2991/icece-16.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Character Values Development in Early Childhood through Traditional Games

Abstract: The importance development of the character values in early childhood is urgent and necessary today, because the condition of the people who are experiencing a crisis of character. Character values that are developed in early childhood is the love of God, Honesty, Discipline , Tolerance and peaceful , Confidence, Self, mutual help, cooperation, and mutual cooperation, respect and courtesy, responsibility, hard work, leadership and justice, Creative, humble, Care for the environment, nationalism. The traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
3
0
5
Order By: Relevance
“…Children had shown their ability to learn and improve values like honesty, tolerance, discipline, curiosity, friendly and hard work. The findings of this study are in line with previous studies on kaulinan barudak implementation to develop children's character (Andriani, 2012;Nur, 2013;Aisyah 2017;Marlina, 2017;Amirudin, Mukarom, 2018).…”
Section: Kaulinan Barudak Application To Teach Character Values In Rasupporting
confidence: 92%
See 1 more Smart Citation
“…Children had shown their ability to learn and improve values like honesty, tolerance, discipline, curiosity, friendly and hard work. The findings of this study are in line with previous studies on kaulinan barudak implementation to develop children's character (Andriani, 2012;Nur, 2013;Aisyah 2017;Marlina, 2017;Amirudin, Mukarom, 2018).…”
Section: Kaulinan Barudak Application To Teach Character Values In Rasupporting
confidence: 92%
“…Several skills can be taught to children using traditional games. Aisyah (2017); Marlina (2017) explored int their study traditional games to build early childhood characters. Saputra, Ekawati, (2017) found that traditional game improved children's basic abilities including interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
“…Pemilihan penggunaan permainan tradisional dalam penelitian ini dikarenakan eksistensi permainan tradisional di zaman modern ini sadang mulai menurun dan kurang diminati oleh anak-anak karena mereka lebih mengenal permainan modern yang terdapat pada gadget. Padahal dalam permainan tradisional terdapat nilai karakter yang relevan dengan nilai-nilai karakter yang perlu dikembangkan pada usia dini (Marlina, 2017). Dalam permainan modern yang terdapat pada gadget yang biasa dimainkan oleh anak hanya melibatkan sebagian kecil aktivitas fisik, berbeda dengan permainan tradisional yang sebagian besar cara mainnya melibatkan aktivitas fisik.…”
Section: Pendahuluanunclassified
“…Game edukatif merupakan salah satu bentuk permainan yang telah dirancang sedemikian rupa yang mengangkat berbagai tema dengan pilihan topik tertentu yang dapat memperluas konsep pemahaman serta keterampilan penggunanya (Kholida et al, 2020;Rekysika & Haryanto, 2019). Manfaat penggunaan game dalam pembelajaran yaitu meningkatkan ketertarikan siswa dalam belajar sehingga mempengaruhi peningkatkan kemampuan kognitif (Gozcu & Caganaga, 2016;Marlina, 2017;Wandini et al, 2021). Selain itu game juga dapat meningkatkan ingatan dan mempengaruhi cara berfikir kreatif pada siswa (Hwang et al, 2013;Kao & Luo, 2020).…”
Section: Pendahuluanunclassified